Interoperabilidade - Capaco, Augusto Eduardo (2018)
The information has always played an important role in the art of governing all along the History. Since the ancient times decision-makers, when wrapped up in agonizing environments, try to acquire knowledge about the mean surrounding them so they can mitigate the imposed uncertainty and, with that, apply the possible measures with the maximum sobriety, in order to achieve objectives or to safeguard interests. Today, just organizations with own characteristics are able to produce intelligence that allow to propose important knowledge to formulate and implement politics directed to the national safety interests, working with the threats and safeguarding the national interests. They should have an organization identified with the one of the main threats: Less hierarchized, netlike, extremely flexible, with an effective and efficient coordination of the research effort, changing its paradigm to be more cooperative, multinational and multidisciplinary. The main objective of the present master´s thesis is to demonstrate the importance and the contribution of systems interoperability in product effectiveness in performance of the Intelligence Organs and State Security. For such, we try to find a comprehension of intelligence concept, as well as the intelligence systems understanding and of State Security. Through a holistic analysis to interoperability in Intelligence, whose focus is its function in OISE's enactments, we can understand that it allows the intelligence share and the reinforcement of the cooperative security in the research, analysis and production intelligence process.